Pengaruh Perceived Lecturer Expertise dan Prior Learning Experience terhadap Purchase Intention yang dimediasi Oleh Performance Expectation: Studi pada Bimbingan Belajar X - A. Ainun Salsabila; Sherly Artadita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of e-learning in Indonesia has grown rapidly which is influenced by innovation by each company. An e-learning system is an instruction or learning experience presented by technology including the internet. One of the tutoring that offers online courses is Bimbel X, which faces challenges in attracting participants to join their program, one of it is Independent Study. Although the quality of materials and lecturer, performance expectations, and previous learning experiences when participants attended webinars or bootcamps have received positive responses, there are still doubts from potential participants in deciding to join the Independent Study program at Bimbel X. To understand the factors that influence their decisions in the Independent Study program at Bimbel X, this study examines the influence of Perceived Lecturer Expertise and Prior Learning Experience on Purchase Intention mediated by Performance Expectation. The method used in this research is descriptive and quantitative with data collection techniques through distributing questionnaires online. The sampling technique used is non-probability sampling using the Slovin formula so that a sample of at least 242 respondents is obtained. The data analysis technique uses descriptive analysis using SEM-PLS with the help of SmartPLS software. Based on the results of descriptive analysis, it is known that there is a favorable correlation between the variable perceived lecturer expertise and purchase intention through performance expectation as evidenced by the T Statistic value of 2.179> 1.96 and P Value of 0.029 <0.05 which means the hypothesis is accepted. Meanwhile, the effect of prior learning experience variables on purchase intention mediated by performance expectation also has a positive and significant effect with a T Statistic value of 2.36> 1.96 and a P Value of 0.018 < 0.05, which means the hypothesis is accepted.